Analysis of control and correction options of mobile robot trajectory by an inertial navigation system. (30th January 2018) - Pivarčiová, Elena; Božek, Pavol; Turygin, Yuri; Zajačko, Ivan; Shchenyatsky, Aleksey; Václav, Štefan; Císar, Miroslav; Gemela, Boris
The article deals with the research of the supplementation of industrial robot effector trajectory's control systems by an inertial navigation system. The method of reverse validation and location of an object in a navigated reference system does not require additional calibration. The goal of the research is to verify the assumption that it is possible to control and correct the programmed mobile robot trajectory by implementing an inertial navigation system even in a case when the inertial navigation system is used as the only trajectory control device. The data obtained are processed by the proposed and detailed application.